EFFECT OF FINANCIAL PERFORMANCE ON STOCK RETURN DURING COVID-19 - Fatrika Januar; Tri Joko Prastyo; Usep Syaipudin (Jurnal Akuntansi dan Pajak, 2022)
This study aims to provide a conceptual study of the effect of financial performance on stock returns during the Covid-19 pandemic. This is evidenced by testing the effect of Earning Per Share (EPS), Operating Cash Flow (OCF), Return On Assets (ROA), and Debt to Assets Ratio (DAR) as independent variables on stock returns in companies listed on the LQ index. 45 Indonesia Stock Exchange. Previous theoretical studies show that stock returns are influenced by the company's financial performance. From the theoretical discussion and previous research, it is concluded that there is a positive influence on the company's financial performance on stock returns. Where there is a decrease in stock returns during the Covid-19 pandemic which is influenced by a decrease in the company's financial performance compared to before the Covid-19 pandemic.